2004
DOI: 10.1210/en.2003-1098
|View full text |Cite
|
Sign up to set email alerts
|

The Volume of a Sexually Dimorphic Nucleus in the Ovine Medial Preoptic Area/Anterior Hypothalamus Varies with Sexual Partner Preference

Abstract: Sheep are one of the few animal models in which natural variations in male sexual preferences have been studied experimentally. Approximately 8% of rams exhibit sexual preferences for male partners (male-oriented rams) in contrast to most rams, which prefer female partners (female-oriented rams). We identified a cell group within the medial preoptic area/anterior hypothalamus of age-matched adult sheep that was significantly larger in adult rams than in ewes. This cell group was labeled the ovine sexually dimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 40 publications
5
109
0
5
Order By: Relevance
“…Studies in the rat SDN-POA inspired the examination of human POA where a nucleus was found that was smaller in women than in men and smaller in gay men than in straight men [14,23]. A similar difference was seen in sheep, POA is smaller in male sheep than prefer to mount other rams than in males that prefer to mount ewes [32]. These observations do suggest that the brain is important for determining sexual orientation and thus this study is relevant to human situation.…”
Section: Brain Regions Preoptic Area Hypothalamus Pituitarymentioning
confidence: 91%
“…Studies in the rat SDN-POA inspired the examination of human POA where a nucleus was found that was smaller in women than in men and smaller in gay men than in straight men [14,23]. A similar difference was seen in sheep, POA is smaller in male sheep than prefer to mount other rams than in males that prefer to mount ewes [32]. These observations do suggest that the brain is important for determining sexual orientation and thus this study is relevant to human situation.…”
Section: Brain Regions Preoptic Area Hypothalamus Pituitarymentioning
confidence: 91%
“…We also calculated the integrated optical density (IOD) of the aromatase in the POM reflecting the aromatase content in the nucleus (Roselli et al, 2004). This was defined as the relative optical density of the aromatase immunoreactivity multiplied by the fractional area covered by the signal within the nucleus and by the total POM volume.…”
Section: Methodsmentioning
confidence: 99%
“…Size of the ovine SDN in male sheep is correlated with subjects' sexual orientation: males with the largest oSDN prefer to seek out and mount an estrous female whereas other males, with significantly smaller oSDNs, showed a spontaneous preference to mount other males instead of females (Roselli et al, 2004a(Roselli et al, , 2004b. It is interesting to note that Fos immunoreactivity in the mPOA/AH was significantly higher in female-oriented than in male-oriented rams that were exposed to the sight, sound and smell of either ewes or other rams (Alexander et al, 2001;Roselli et al, 2011).…”
Section: Sex Differences In Sexual Partner Preference: Contribution Omentioning
confidence: 99%